2021
DOI: 10.1038/s41418-021-00782-3
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein dictates syncytium-mediated lymphocyte elimination

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus is highly contagious and causes lymphocytopenia, but the underlying mechanisms are poorly understood. We demonstrate here that heterotypic cell-in-cell structures with lymphocytes inside multinucleate syncytia are prevalent in the lung tissues of coronavirus disease 2019 (COVID-19) patients. These unique cellular structures are a direct result of SARS-CoV-2 infection, as the expression of the SARS-CoV-2 spike glycoprotein is sufficient to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
161
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(172 citation statements)
references
References 48 publications
8
161
1
2
Order By: Relevance
“…The histology of 41 lung samples from COVID-19 patients show that 87% of them display dysmorphic pneumocytes with syncytia (Bussani et al, 2020). In vitro studies have also shown syncytia formation in hiPSC-derived neurons, hiPSC-derived astrocytes, U2OS-ACE2, Vero-ACE2, and 293T-ACE2 after viral infection (Buchrieser et al, 2020;Wang et al, 2021;Zhang et al, 2021). Recent papers propose that a unique bi-arginine motif within the S1/S2 cleavage site of SARS-CoV-2 spike glycoprotein mediates the fusion of neighboring ACE2 + cells and formation of syncytia (Braga et al, 2021;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The histology of 41 lung samples from COVID-19 patients show that 87% of them display dysmorphic pneumocytes with syncytia (Bussani et al, 2020). In vitro studies have also shown syncytia formation in hiPSC-derived neurons, hiPSC-derived astrocytes, U2OS-ACE2, Vero-ACE2, and 293T-ACE2 after viral infection (Buchrieser et al, 2020;Wang et al, 2021;Zhang et al, 2021). Recent papers propose that a unique bi-arginine motif within the S1/S2 cleavage site of SARS-CoV-2 spike glycoprotein mediates the fusion of neighboring ACE2 + cells and formation of syncytia (Braga et al, 2021;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also shown syncytia formation in hiPSC-derived neurons, hiPSC-derived astrocytes, U2OS-ACE2, Vero-ACE2, and 293T-ACE2 after viral infection (Buchrieser et al, 2020;Wang et al, 2021;Zhang et al, 2021). Recent papers propose that a unique bi-arginine motif within the S1/S2 cleavage site of SARS-CoV-2 spike glycoprotein mediates the fusion of neighboring ACE2 + cells and formation of syncytia (Braga et al, 2021;Zhang et al, 2021). Furthermore, previous studies have found that syncytia mediated by SARS-CoV-2 as well as other viruses such as human immunodeficiency virus-1 (HIV-1) and reovirus-associated FAST proteins can lead to apoptosis (Scheller and Jassoy, 2001;Salsman et al, 2005;Nardacci et al, 2015;Buchrieser et al, 2020), This suggests that apoptosis in virus infected cultures becomes exacerbated via syncytia formation and cytopathy affects can be alleviated by targeting the relevant downstream processes specific to that cell type and virus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CIC structures are also regarded as a way for tissues to maintain homeostasis (29,30). Disorder in this process may lead to tumors or diseases such as immune-related disorders (8,(31)(32)(33). At present, literatures have reported CIC structures in tumor tissues, including urothelial carcinoma (34), buccal mucosa squamous cell carcinoma (10), pancreatic ductal adenocarcinoma (9), metastatic adenocarcinoma (34), head and neck squamous cell carcinoma (35), renal cell carcinoma (36), gastric cancer (37), breast carcinoma (11,38), small cell carcinoma of lung (39), benign tendon sheath giant cell carcinoma specimen (40), malignant mesothelioma (41), leiomyolipoma (42), etc., but there is no study on the CIC structures in the tissues of esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CIC formation as a mechanism of cell cannibalism that is induced by the establishment of epithelial adhesion could inhibit transformed growth, suggesting that CIC structuremediated cell killing might also be a potential tumor suppressive pathway (7,20). Cannibalistic behavior, as one of the mechanisms involving CIC formation, may increase nutrient intake by feeding upon other cells, and escape from the specific immune response by engulfing lymphocytes (33). In this scenario, upregulation of phagocytosis in human tumor cells may be similar to that of some unicellular microorganisms, of which the goal is to survive and propagate in a hostile microenvironment (8,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which the SARS-CoV-2 S protein regulates the formation of these syncytia is not fully clear. A study has found that SARS-CoV-2 S protein mediated lymphocyte elimination through syncytia (7). Infected cells form syncytia through membrane fusion with minimal S protein, making be challenging to obtain neutralizing antibodies and prevent them through antibodies effectively (8).…”
Section: Introductionmentioning
confidence: 99%